2020
DOI: 10.2215/cjn.06480619
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance Guided Fluid Management in Peritoneal Dialysis

Abstract: Background and objectivesBioelectrical impedance analysis (BIA) devices can help assess volume overload in patients receiving maintenance peritoneal dialysis. However, the effects of BIA on the short-term hard end points of peritoneal dialysis lack consistency. This study aimed to test whether BIA-guided fluid management could improve short-term outcomes in patients on peritoneal dialysis.Design, setting, participants, & measurementsA single-center, open-labeled, randomized, controlled trial was conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…BIA is commonly used in dialysis patients to guide fluid management by calculating dry weight goals [ 11 , 44 ]. Likewise, in critical illness PhA, ECW/TBW ratio and overhydration could be used to monitor the effect of fluid management strategies.…”
Section: Fluid Managementmentioning
confidence: 99%
“…BIA is commonly used in dialysis patients to guide fluid management by calculating dry weight goals [ 11 , 44 ]. Likewise, in critical illness PhA, ECW/TBW ratio and overhydration could be used to monitor the effect of fluid management strategies.…”
Section: Fluid Managementmentioning
confidence: 99%
“…The intervention period was relatively short, and some subjects in the study group still had a higher nECW than the target level, and had HTN even though BP improved. Tian et al also reported that BIA assistant intervention does not change a 1-year survival rate in PD [46]; therefore, it is difficult to conclude that BIA assistant dry-weight setting can provide a long-term survival benefit. Lastly, fluid control in the study group was lost in the maintenance phase, which makes the long-term effect of strict dry-weight control on RRF unviable.…”
Section: Discussionmentioning
confidence: 99%
“… 37 Although a trial of 131 HD patients found improvements in overall survival among patients in the BIA arm at 2.5 years of follow-up, 38 a recent trial that followed up 240 patients receiving PD over 1 year showed no differences in CV events or all-cause mortality. 39 Because these studies were limited by modest sample size (and more importantly, the modest number of events) and focused on prevalent dialysis patients, there is a need for large-scale randomized controlled trials to determine whether optimizing volume status using BIA improves clinical outcomes among patients with CKD initiating maintenance dialysis.…”
Section: Discussionmentioning
confidence: 99%